The Role of Budgetary Participation and Environmental Uncertainty in Influencing Managerial Performance of Village Government - Hafiez Sofyani; Muhamad Fandi Indra Santo Simali; Taufik Najda; Mohammed Saleh Al-maghrebi (Journal of Accounting and Investment, 2020)
Research aims: This study aims to examine the influence of budgetary participation and environmental uncertainty on the managerial performance of the village government. In addition, it examines the budgetary participation as an intervening variable.